Preparing bulk Cu-Ni-Mn based thermoelectric alloys and synergistically improving their thermoelectric and mechanical properties using nanotwins and nanoprecipitates. (March 2021) - Kang, H.; Yang, Z.; Yang, X.; Li, J.; He, W.; Chen, Z.; Guo, E.; Zhao, L.-D.; Wang, T.
Abstract: Cu-Ni-Mn based alloys have long been considered as potential thermoelectric materials because of their Seebeck effect and large power factor. In this study, bulk Cu-Ni-Mn based alloys with nanostructures were prepared via melting and cryorolling, and their thermoelectric and mechanical properties were analyzed. A large number of nanotwins and nanoprecipitates were observed in the prepared alloys using transmission electron microscopy. These observations indicate that the bulk Cu-Ni-Mn alloys with nanostructures can be successfully prepared using conventional melting-solidification-rolling technology. The Cu-Ni-Mn alloy containing nanotwins exhibits a promising Seebeck coefficient of ∼ −72.8 μVK −1 and power factor of ∼11000 μWm −1 K −2 at 1073 K, and thereby, a high output power density. The bulk Zr-doped Cu-Ni-Mn alloy containing nanoprecipitates and nanotwins exhibits a lower thermal conductivity of ∼32.9 Wm −1 K −1 and a 37.5% higher ZT of ∼0.22 at 773 K. Enhanced mechanical properties make the Cu-Ni-Mn based alloys a promising candidate for thermoelectric application. Our discovery provides a promising strategy to improve the thermoelectric and mechanical properties of materials with high thermal conductivity through the introduction of nanotwins and nanoprecipitates. Graphical abstract: Bulk Cu–Ni–Mn based alloys with nanotwins and nanoprecipitates are successfully prepared using conventional melting-solidification-rolling technology. The low-energy carriers and phonons are scattered by these nanostructures, leading to a conspicuous enhancement of TE performance for Cu–Ni–Mn based alloys. Image 1 Highlights: Bulk Cu–Ni–Mn thermoelectric alloys with nanostructures were prepared by melting and cryorolling. Nanotwins were introduced to improve thermoelectric properties. Thermal conductivity was significantly lowered through forming nanoprecipitates. A maximum ZT value of 0.22 at 773 K was reached in Cu–Ni–Mn alloy. Both excellent thermoelectric and mechanical properties were obtained for the Cu–Ni–Mn alloy.